2021
DOI: 10.1073/pnas.2015931118
|View full text |Cite
|
Sign up to set email alerts
|

Structure and assembly of the diiron cofactor in the heme-oxygenase–like domain of the N -nitrosourea–producing enzyme SznF

Abstract: In biosynthesis of the pancreatic cancer drug streptozotocin, the tridomain nonheme-iron oxygenase SznF hydroxylates Nδ and Nω′ of Nω-methyl-l-arginine before oxidatively rearranging the triply modified guanidine to the N-methyl-N-nitrosourea pharmacophore. A previously published structure visualized the monoiron cofactor in the enzyme’s C-terminal cupin domain, which promotes the final rearrangement, but exhibited disorder and minimal metal occupancy in the site of the proposed diiron cofactor in the N-hydrox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 56 publications
5
55
0
Order By: Relevance
“…Our findings resemble the discovery that the HD domain family of enzymes, which were presumed to be metalloenzymes with phosphohydrolase activity, encompass members with iron-dependent oxygenase activity (49)(50)(51)(52). The discovery of an activity of a PHP family member that is very different from previously reported activities, as well as the phylogenetic analysis, suggests that this enzyme superfamily may catalyze a much larger set of reactions than previously appreciated and adds to the known folds that support dinuclear iron chemistry (32,34,53,54).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our findings resemble the discovery that the HD domain family of enzymes, which were presumed to be metalloenzymes with phosphohydrolase activity, encompass members with iron-dependent oxygenase activity (49)(50)(51)(52). The discovery of an activity of a PHP family member that is very different from previously reported activities, as well as the phylogenetic analysis, suggests that this enzyme superfamily may catalyze a much larger set of reactions than previously appreciated and adds to the known folds that support dinuclear iron chemistry (32,34,53,54).…”
Section: Discussionsupporting
confidence: 75%
“…The distance between the two Fe atoms is 4.9 Å, which is considerably longer than the 2.5 to 3.4 Å distances observed in canonical nonheme diiron enzymes (SI Appendix, Table S1) (32). However, similar long Fe-Fe separation distances have been reported in the structures of diiron-reconstituted UndA (33) and SznF (34). In the case of UndA, binding of the substrate triggers the formation of a μ-peroxo-Fe(III/III) with an Fe-Fe separation of 3.21 Å, as determined by extended X-ray absorption fine structure studies.…”
Section: Resultssupporting
confidence: 59%
“…1 A strategy of (i) preparing naive apo protein by heterologous expression in low-iron medium supplemented with Mn(II) to occupy the metal sites and prevent potentially deleterious cofactor cycling during protein production, (ii) chelation of the bound Mn(II) from the purified protein, (iii) crystallization of the apo protein, and (iv) soaking of crystals with Fe(II) yielded a structure of the SznF•Fe(II) 2 complex with both sites almost fully occupied, the first such structure of an HDO. 26 Comparison of apo and metallated structures revealed that one of the iron sites in the HDO domain (site 2) is not pre-formed (Fig. S1), by contrast to observations made on structures of apo FDOs.…”
Section: Introductionmentioning
confidence: 64%
“…This dichotomy within the first two mechanistically characterized HDOs mirrors that seen in the FDOs, of which the N-oxygenases AurF and CmlI were shown not to require triggering by either the substrate or an accessory protein. 24 Recent x-ray crystallographic studies of SznF 26 shed light on the instability of the diiron cofactor in its HDO domain, 19 and structural characteristics shared with UndA 18,23 suggested that the insight might be general to other (potentially all) enzymes in the emerging HDO family. 1 A strategy of (i) preparing naive apo protein by heterologous expression in low-iron medium supplemented with Mn(II) to occupy the metal sites and prevent potentially deleterious cofactor cycling during protein production, (ii) chelation of the bound Mn(II) from the purified protein, (iii) crystallization of the apo protein, and (iv) soaking of crystals with Fe(II) yielded a structure of the SznF•Fe(II)2 complex with both sites almost fully occupied, the first such structure of an HDO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation